Performance of Retrofitted Self-Compacting Concrete-Filled Steel Tube Beams Using External Steel Plates - Ahmed A. M. AL-Shaar; Mehmet Tolga Göğüş (Advances in Materials Science and Engineering)
Self-compacting concrete-filled steel tube (SCCFST) beams, similar to other structural members, necessitate retrofitting for many causes. However, research on SCCFST beams externally retrofitted by bolted steel plates has seldom been explored in the literature. This paper aims at experimentally investigating the retrofitting performance of square self-compacting concrete-filled steel tube (SCCFST) beams using bolted steel plates with three different retrofitting schemes including varied configurations and two different steel plate lengths under flexure. A total of 18 specimens which consist of 12 retrofitted SCCFST beams, three unretrofitted (control) SCCFST beams, and three hollow steel tubes were used. The flexural behaviour of the retrofitted SCCFST beams was examined regarding flexural strength, failure modes, and moment versus deflection curves, energy absorption, and ductility. Experimental results revealed that the implemented retrofitting schemes efficiently improve the moment carrying capacity and stiffness of the retrofitted SCCFST beams compared to the control beams. The increment in flexural strength ranged from 1% to 46%. Furthermore, the adopted retrofitting schemes were able to restore the energy absorption and ductility of the damaged beams in the range of 35% to 75% of the original beam ductility. Furthermore, a theoretical model was suggested to predict the moment capacity of the retrofitted SCCFST beams. The theoretical model results were in good agreement with the test results.